2020
DOI: 10.1016/j.kint.2019.11.013
|View full text |Cite
|
Sign up to set email alerts
|

IL-6-mediated hepatocyte production is the primary source of plasma and urine neutrophil gelatinase–associated lipocalin during acute kidney injury

Abstract: A cute kidney injury (AKI) is a common complication in hospitalized patients, occurring in up to 20% of hospital admissions and 30% to 50% of intensive care unit admissions. AKI is an independent risk factor for death, with mortality rates as high as 50% in the intensive care unit. 1 The development of biomarkers that can identify AKI early and more reliably than serum creatinine rise has been a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 41 publications
(57 reference statements)
0
26
0
Order By: Relevance
“…Based on their result, they predicted that NGAL levels may increase regardless of whether AKI occurs in conditions wherein plasma IL-6 levels can increase. Those authors reported the need for further studies to validate this result with regard to AKI in the general [12].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Based on their result, they predicted that NGAL levels may increase regardless of whether AKI occurs in conditions wherein plasma IL-6 levels can increase. Those authors reported the need for further studies to validate this result with regard to AKI in the general [12].…”
Section: Discussionmentioning
confidence: 90%
“…In a basic research study by Skrypnyk et al, interleukin-6 (IL-6) was shown to mediate hepatic NGAL production in AKI in a mice. Those authors reported that hepatocytes are the primary source of plasma and urine NGAL during AKI [12]. However, AKI is a highly complex systemic disorder, and there are limitations with regard to the generalizability of the abovementioned results.…”
Section: Introductionmentioning
confidence: 99%
“…In diabetic patients, NGAL produced in tubules could be released in the urine or may reflect proximal tubule dysfunction leading to urinary leak of filtered plasma NGAL, which, as recently shown, is produced in hepatocytes driven by IL-6. 17 In nondiabetic CKD, a recent study on autosomal-dominant polycystic kidney disease patients found MCP1 as a strong predictor of progression. 18 Our linear regression mixed models using a larger number of observations demonstrated significant associations between ACR, RBP, and MCP1 and CKD progression (to stage 3 or 4) in the whole cohort and MCP1 in the ACR <3 cohort but not NGAL or IL-6, as shown in logistic regression models.…”
Section: Discussionmentioning
confidence: 99%
“…NGAL can be found in blood and urine in several forms: a homodimer of two combined NGAL molecules and/or a heterodimer of NGAL combined with lipocalin (typically of neutrophil original) and/or a monomer of NGAL alone (essentially of tubular origin) 19 . NGAL is also complex in its origin because, even though it can be released into the tubular lumen or, perhaps into the blood stream from the tubules, it is also released by neutrophils under conditions of activation, and most of all by the liver in conditions of inflammation (an interleukin‐6 dependent process) 20 and in a form that can be filtered by the glomerulus. Moreover, if filtered, its absorption is regulated by the expression and availability of megalin, a binding protein that can easily be made less available by the presence of proteinuria 21 .…”
Section: What Do Novel Aki Biomarkers Represent?mentioning
confidence: 99%